Public Archaeology 2015: Letting public engagement with archaeology 'speak for itself' - Lorna-Jane Richardson; James Dixon (Internet Archaeology, 2017)
Public Archaeology 2015 was a year-long project dedicated to the creation of public engagement and involvement with archaeological projects and subjects. Month-long projects were devised and enacted by both archaeologists and non-archaeologists, with the impact of the project residing in the moments of engagement themselves rather than critical or academic analysis with the benefit of hindsight. In this short article, the convenors of the project discuss the project's central ethos and its relationship to wider debates on co-production and impact assessment in public archaeology. It expands discussion on the opposition therein between impetus provided by 'experts' and from 'amateurs'. The project aimed to use a different mode of operation to existing 'top-down' or 'bottom-up' models of collaboration, and created a democratic situation where different kinds of public engagement with archaeology took place within a wider context of those central terms — public, archaeology, engagement — being kept intentionally fluid and open to interpretation.